A fully automated and generic spatial discretization procedure for cultivated landscapes with human-made landscape elements. Issue 4 (11th July 2022) - Lagacherie, Philippe; Dagès, Cécile; Zadonina, Ekatarina; Fabre, Jean Christophe; Molénat, Jérôme; Squividant, Hervé; Thomas, Bruce
Abstract: Landscape discretization is an essential hydrological modeling pre-processing step that comprises the numerical representation of different geographical objects considered in the modeling process and the connections between these objects within a graph structure. GROOV'Scape is a new landscape discretization procedure that (i) produces an oriented tree of a wide range of human-made landscape elements, such as plots, hedges, benches, grass stripes, and ditches, (ii) is fully automated to avoid local drainage anomalies that require user corrections, and (iii) is fast enough to enable sensitivity analysis and the interactive production of mediated modeling landscape management scenarios. GROOV'Scape was tested on a small agricultural catchment in south-west France (Doazit catchment, 9.05 km 2 ). The results show good agreement between the connections of areal units computed by GROOV'Scape and those observed in the field. The system exhibited substantial sensitivity to the user's choice of minimum area unit size and of digital elevation model (DEM) resolution, suggesting trial-and-error approaches are needed to reach the best landscape discretization for any given modeling purpose. Finally, we demonstrated the feasibility of using GROOV'Scape to find an optimum configuration of an infrastructure network with respect to a given ecosystem function. HIGHLIGHTS: GROOV'Scape produces an oriented tree of human-made landscape elements. Fully automated and fast for sensitivity analysis and exploration of scenarios. Good agreement of GROOV'Scape-oriented trees with field observations. Trial-and-error approaches are needed to reach the best landscape discretization. GROOV'Scape helps to find an optimum configuration of an infrastructure network.